PENGARUH TATA RUANG KANTOR DAN FASILITAS KERJA TERHADAP KEPUASAN KERJA PEGAWAI BAGIAN UMUM PADA PDAM TIRTAULI PEMATANGSIANTAR - Diah Pratiwi; Darwin Lie; Marisi Butarbutar; Andy Wijaya (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2019)
The results of the study can be summarized as follows: 1) Office layout, job facilities are excellent and job satisfaction is satisfied. 2) The results of the regression analysis are Ŷ = 2,648 + 0,759X1 + 0,136X2 meaning that office layout and job facilities have a positive and significant effect on employees job satisfaction. 3) The results of the correlation analysis obtained nilai r = 0.767, meaning that there is a strong and positive relationship between office layout and job facilities with employees job satisfaction. 4) Obtained the coefficient of determination R =0,589 means that Employees job satisfaction can be explained by office layout and job facilities by 58,9%. 5) The research hypothesis H0 is rejected, meaning that office layout and job facilities have a positive and significant effect on employees job satisfaction in PDAM Tirtauli Pematangsiantar both simultaneously and partially. Keywords: Office Layout, Job Facilities, and Job Satisfaction